The Effect of Mosaic Activities on Fine Motor Skills of Group A Children at AL-HIKMAH Kindergarten, Cipeucang - Dian Fitri; Siti Mutmainah; Laxmi Permata Sari Suardi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to examine the effect of mosaic activities on the fine motor development of children at AL-HIKMAH Kindergarten. Fine motor skills involve the coordination of small muscles, particularly in the hands and fingers, which are essential for daily activities such as writing, drawing, and handling objects. This research employed a quantitative method with a quasi-experimental approach. Data were collected using activity sheets completed by the children during the mosaic sessions. The data were analyzed using a t-test, which showed a significant difference after the mosaic activities were implemented. Children who participated in the mosaic activities demonstrated greater improvement in fine motor skills compared to those who did not. These results indicate that mosaic activities have a positive impact on the fine motor development of kindergarten-aged children. The findings are expected to serve as a useful reference for teachers and early childhood education practitioners in designing learning activities that support children's motor skill development